A função exponencial no caderno do professor de 2008 da Secretaria do Estado de São Paulo, análise de atividades realizadas por alunos da 2ª série do ensino médio - Souza, Cláudia Vicente de (2010)
This work arms is to analyze whether the activities presented in the Teacher´s Book contribute to the student´s on not understanding about the exponential function, and whether on not the students can make changes in the register of semiotic representation, according to Duval´s theory (2003). We also analyze if there is a variable approach in this book according to the Ursini´s et al (2005) 3UV model (Three Uses for the Variable). Our interest in doing this research started with the observation in classroom of the students´ low performance related to the studies of the functions and the analysis of the evaluations done by the São Paulo State Government, such as SARESP/2007, which presented as results Math students´ low academic performance. The research instrument consists of a review activity of powers and four activities related to the exponential function introduction, which are found in the Math Teacher´s Book of the High School first grade, third quarter of 2008. This document belongs to the São Paulo´s New Curriculum Proposal, 2008. The research presents a qualitative approach, using the methodology of Artigue´s Didactic Engineering (1996). The study counted on 14 high school students of the second grade from a state school located on the outskirts of the northwest region of São Paulo. Upon the results, we found out that there are difficulties in achieving changes in register of semiotic representation (register of the natural language for the algebraic register, register of table to register chart) and limitations regarding the identification of the variables as a functional relationship and unknown term. We believe that is the reflection of the difficulties which started from the beginning of the functions studies. As a positive aspect, we verified that some pairs in their graphic constructions approached the graph of the exponential function, thus demonstrating that they understand the idea of this function behavior